O Olhar do "outro" sobre si mesmo: as representações de América nos manuais de formação de professores no Brasil e na Argentina (1900-1913) - Santos, Analice Alves Marinho (2013)
This work aims identifying the representation about America in manuals intended for teachers formation which are writing by the brazilian José Francisco da Rocha Pombo (1857-1933) and by the argentinian Carlos Navarro y Lamarca (1868-1921). Following the Roger Chartier orientations, I analyzed the representation about the America in the didactic manuals Compendio de Historia da America (1900) by Rocha Pombo and Compendio de la Historia General de América (1910/1913) by Carlos Lamarca. The methodology that I used to find these representations was through the analyses of events about american history in each manual and compared the representations intending to answer the question: what are the representation about America in the brazilian and argentinian manuals? The research results indicate that Rocha Pombo and Carlos Lamarca conceive two different Americas : the first argues that before the colonization, the America could be separated by geographic localization and after colonization there are two Americas ": one colonized by Iberian and another by the British. To Lamarca, the independence changes the representation of America: before emancipation the "Americas" are differentiated too the according to their geographic location and with the independence the continent is represented through particular stories and North America. I believe that the study of representations of America is something necessary for understanding how generalizations and negative expressions were built in order to not only know and disseminate the American experience, but also modify the teaching of American History in Brazil and Argentina. Thus, identifying the representations on the continent, I think it is possible to locate the social spaces where they were written and the social groups that created, comprising thus their deeper meanings.